2011
DOI: 10.1007/s10802-011-9499-1
|View full text |Cite|
|
Sign up to set email alerts
|

Emotion Regulation via the Autonomic Nervous System in Children with Attention-Deficit/Hyperactivity Disorder (ADHD)

Abstract: Despite growing interest in conceptualizing ADHD as involving disrupted emotion regulation, few studies have examined the physiological mechanisms related to emotion regulation in children with this disorder. This study examined parasympathetic and sympathetic nervous system reactivity via measures of respiratory sinus arrhythmia (RSA) and cardiac pre-ejection period (PEP) in children with ADHD (n=32) and typically developing controls (n=34), using a novel emotion task with four conditions: negative induction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
153
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(172 citation statements)
references
References 57 publications
11
153
0
2
Order By: Relevance
“…This experimental manipulation varies the interpersonal stress and is analogous to studies of mood induction and emotional regulation (Musser et al, 2011) and with prior research on disruptive behavioral disorders across interpersonal settings (Wakschlag et al, 2008). Observed behaviors indicating anger/irritability and warmth/engagement were coded in each of the three settings by raters blind to all clinical and diagnostic data.…”
Section: Observational and Experimental Findingsmentioning
confidence: 99%
“…This experimental manipulation varies the interpersonal stress and is analogous to studies of mood induction and emotional regulation (Musser et al, 2011) and with prior research on disruptive behavioral disorders across interpersonal settings (Wakschlag et al, 2008). Observed behaviors indicating anger/irritability and warmth/engagement were coded in each of the three settings by raters blind to all clinical and diagnostic data.…”
Section: Observational and Experimental Findingsmentioning
confidence: 99%
“…Some studies have assessed HRV in ADHD and have shown that there is autonomic dysregulation. Studies carried out by Shibagaki and Furuya [19] , Beauchaine et al [20] , Buchhorn et al [21,22] and Musser et al [23] showed decreased vagal tone in ADHD. However, studies carried out by Börger et al [24] , Crowell et al [25] , Negrao et al [26] and Wang et al [27] show that there is parasympathetic overarousal in ADHD.…”
mentioning
confidence: 91%
“…The Methylphenidate is one of the most commonly used medications for ADHD treatment 5 . Studies on autonomic functions have shown that stimulant-free children with ADHD showed a sympathetic under arousal and parasympathetic over arousal relative to control subjects and Methylphenidate shifted the autonomic balance of children with ADHD towards normal levels [6][7][8] . The abbreviated version of…”
Section: Introductionmentioning
confidence: 99%